Bacterial Modulation of the Plant Ethylene Signaling Pathway Improves Tolerance to Salt Stress in Lettuce (Lactuca sativa L.) - Fortt, Jonathan; González, Máximo; Morales, Paloma; Araya, Nelson; Remonsellez, Francisco; Coba de la Peña, Teodoro; Ostria-Gallardo, Enrique; Stoll, Alexandra (Frontiers in Sustainable Food Systems, 2022)
Salinity has extensive adverse effects on plant growth and the development of new agronomic strategies to improve crop salt tolerance is becoming necessary. Currently, the use of plant growth promoting rhizobacteria (PGPR) to mitigate abiotic stress in crops is of increasing interest. The most analyzed mechanism is based on ACC deaminase activity, an enzyme that decreases the ethylene synthesis, an important phytohormone in plant stress response. We aimed to identify other PGPR mediated mechanisms involved in the regulation of salt stress in plant. We used three PGPR strains (ESL001, ESL007, SH31), of which only ESL007 demonstrated ACC deaminase activity, to evaluate their effect on lettuce plants under salt stress (100 mM NaCl). We measured growth and biochemical parameters (e.g. proline content, lipid peroxidation and ROS degradation), as well as expression levels of genes involved in ethylene signaling (CTR1, EBF1) and transcription factors induced by ethylene (ERF5, ERF13). All bacterial strains enhanced growth on salt-stressed lettuce plants and modulated the proline levels. Strains ESL007 and SH31 triggered a higher catalase and ascorbate-peroxidase activity, compared to non-stressed plants. Differential expression of ethylene-related genes in inoculated plants subjected to salinity was observed. We gained consistent evidence for the existence of alternative mechanisms to ethylene modulation, which probably rely on bacterial IAA production and other chemical signals. These mechanisms modify the expression of genes associated with ethylene signaling and regulation, complementarily to the ACC deaminase model to diminish abiotic stress responses.